Degeneration of Intramural Pericytes in Diabetic Retinopathy. Issue 5691 (31st January 1970) - Addison, D. J.; Garner, A.; Ashton, N.
Abstract : Retinal pericyte degeneration, a usual finding in diabetic retinopathy, has been shown to be a change probably peculiar to the retina rather than part of a more widespread angiopathy. Thus in a patient with diabetic retinopathy the characteristic eosinophilic degeneration of the pericyte nuclei ceased at the optic disc and could not be found in vessels of the optic nerves and brain.